AICCRA Ethiopia Stakeholder Consultation Report - Makonnen, Brook T.; Radeny, Maren A.O.; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The AICCRA Ethiopia cluster stakeholder consultation meeting was held on September 26, 2023, at the International Livestock Research Institute in Addis Ababa, Ethiopia. The half-day consultation meeting brought together various partners and stakeholders from around the country drawn from diverse organizations. The partner consultation is a critical component of the project development and aimed to: (i) Update and inform, in general, our stakeholders about the AICCRA program, including its unique model for research and innovation development, helping to bridge the “missing middle” between science and action and to be an efficient way to support regional African organizations and governments to deliver research and innovation to beneficiaries, integrating gender and social inclusion strategies and approaches; (ii) Inform our partners and stakeholders about the continuation of financing and the rationale for AICCRA’s AF, including the new orientations and increased ambitions i.e., (a) transitioning from “access” to validated CSA and CIS technologies to include “their uptake and use” by beneficiaries and end users, (b) focusing on the strengthening of the regional organizations to provide direct support to beneficiaries for sustainability, and (c) expanding AICCRA support to target government programs and priorities; and (iii) Collect inputs and feedback from the stakeholders to consolidate into AICCRA’s AF proposal.